Discovery of porcine proteins-binding DNA aptamer through SELEX and proteomics for pork authentication - Mohamad, Nornazliya; Hashim, Amalia Mohd; Khairil Mokhtar, Nur Fadhilah; Yuswan, Mohd Hafis; Mustafa, Shuhaimi (Elsevier Inc., 2024)
The authentication of meat products has become a global consumer concern in the food industry. Traditional methods such as PCR and mass spectrometry can identify and differentiate the source of meat, but they are time-consuming and require high-quality extracted DNA or protein for testing. As an alternative, aptamer-based detection tools have been introduced, but their application in food authentication is still new. To date, there is a lack of data on the development of a porcine-specific aptamer that is specifically bound to a heat-stable protein. Hence, this study was conducted to screen, characterize and validate aptamers bound to any pork protein through SELEX process, combined with Next Generation Sequencing (NGS) and Liquid Chromatography Mass Spectrometry (LC-MS) analysis. The putative porcine-specific aptamers were selected after fourteen rounds of selection using centrifugal-ultrafiltration separation technique against five negative controls. The binding affinity test revealed that APT#A1 had the highest binding affinity with a dissociation constant of 27.61 ± 1.92 nM. However, the protein blotting results showed that the selected porcine-bound aptamers were not specific and could also bind to multiple proteins from negative samples. LC-MS analysis showed that the aptamers bound to troponin and tropomyosin subunits, and these proteins have potential as target markers for future authentication studies. Future research can focus on developing aptamers with higher specificity towards porcine protein and validating their feasibility as a practical tool for food authentication in real meat-based food samples.